Evaluating Coaching Achievement Taekwondo Sports Branch of Students Development Center and Sport Training NTT (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2019)
This study aims to: evaluate the antecedent, PPLP NTT taekwondo sporting achievement program which includes athletes and coaches, financing, facilities and infrastructure, evaluating transactions, controlling training and learning processes, calmness, training planning programs, consumption, promotion and degradation, transportation and coordination, evaluating outcomes, namely achievements in sports and academic fields. This study is a program evaluation research, with qualitative research methods, the model of the approach used is the evaluation of model maintenance, the source of the research data is the management, trainers and athletes. Data collection techniques are observation, interviews, documentation and data circulation. The results of this study are: antecedent, including the selection of athletes and coaches going well because they are selected based on the terms and conditions that apply, poor infrastructure and facilities due to unavailability of buildings and mattresses for training, good sources of funds because the source of funds comes from Kemenpora and APBD , transaction, covering the control of the learning exercise process in accordance with what was determined, the calm has been going well because in the dormitory there are those who control, the implementation of the training program is very good because there is an exercise program, funding/funding is good enough, consumption and transportation are good, coordination has gone well, the outcome, the achievements of athletes in the field of sports have decreased performance and are not stable because they have not reached the expected target, achievement in the academic field is good enough. The conclusion is that: Antecedents, selection of athletes and coaches that are feasible because they are selected through a selection process in accordance with the appropriate provisions, facilities and infrastructure are still not fully fulfilled, for funding has gone well, funds come from Kemenpora and supported by NTT provincial APBD funds. Transaction control of the training and learning process has been going well, the trainer is always required by the board to take part in trainings, the administrators always provide counseling related to nutrition and psychology to athletes, calmness is running well because there is control, the implementation of the training program has been running according to what has been determined by the trainer, consumption, promotion and degradation is already underway with what is stipulated by PPLP NTT, transportation is quite good, coordination has gone well without any significant obstacles. Outcome, achievement in the field of sports has decreased, for achievement in the academic field is quite good because there has been no degradation through academic achievement.